Genetic analysis of reproductive characteristics in Iran-Black sheep (Acta Scientiarum. Animal Sciences, 2020)
This study was conducted to estimate genetic parameters and trends for reproduction traits using data collected at the breeding station of Iran-Black sheep during 1980 to 2004. The traits included in the analyses were litter size at birth (LSB) and weaning (LSW) and litter mean weight per lamb born (LMWLB) and weaned (LMWLW) as basic traits, and total litter weight at birth (TLWB) and weaning (TLWW) as composite traits. Direct heritability estimates for LSB, TLWB, LMWLB, LSW, TLWW and LMWLW were 0.11, 0.07, 0.33, 0.08, 0.09 and 0.11, respectively. The permanent environmental effects had significant impact on all traits and ranged from 0.05 to 0.16. Effect of service sire was highly significant (p < 0.01) for all traits except LMWLW. Estimates of genetic correlations ranged from -0.76 (LSB-LMWLB) to 0.98 (LSB-LSW). Phenotypic and environmental correlations were generally lower than those of genetic correlations. Environmental correlations ranged from -0.55 (LSW-LMWLW) to 0.99 (LSB-LSW). Also, the estimated correlation for the effect of service sire ranged from -0.77 (LMWLB-TLWW) to 0.96 (LSB-LSW and LSB-TLWW). The results suggest that selection based on TLWB could be more effective than the other traits to enhance reproductive performance in Iran-Black ewes.